MEDIATING ROLE OF CUSTOMER SATISFACTION AND ITS IMPACT TOWARDS BRAND IMAGE OF FRIED CHICKEN RESTAURANT - Idris Gautama So; Eric Putra; Ishak Ismail (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2010)
Customer satisfaction is a very important issue in industries including food industry. This research is aimed to analyze the mediating role of customer satisfaction in order to have loyal returning customers. Objectives of this research is to analyze the influence of service quality and product quality to customer satisfaction and its impacts towards retaurant’s brand image. Pearson correlation and Path Analysis are used in this research. Samples of this research are visiting customers of ”KD” Fried Chicken restaurant. Data is collected using questionnaires filled by the visiting customers with choosing the answer in likert scale. The result of this research shows product quality has a strong relationship and significant contribution in influencing customer satisfaction and brand image. Customer satisfaction also has a strong relationship and contributed to brand image, while service quality has no contribution to both customer satisfaction and brand image of Fried Chicken restaurant, thus this research suggest the improvement of service quality towards the existing customers to achive customers satisfaction and brand image, and give some other beneficial inputs to the restaurant which may be resulted in customer satisfaction and better brand image in the future.